Biomarkers and diagnostic guidelines for sporadic Creutzfeldt-Jakob disease. Issue 3 (March 2021) - Hermann, Peter; Appleby, Brian; Brandel, Jean-Philippe; Caughey, Byron; Collins, Steven; Geschwind, Michael D; Green, Alison; Haïk, Stephane; Kovacs, Gabor G; Ladogana, Anna; Llorens, Franc; Mead, Simon; et al.
Summary: Sporadic Creutzfeldt-Jakob disease is a fatal neurodegenerative disease caused by misfolded prion proteins (PrP Sc ). Effective therapeutics are currently not available and accurate diagnosis can be challenging. Clinical diagnostic criteria use a combination of characteristic neuropsychiatric symptoms, CSF proteins 14-3-3, MRI, and EEG. Supportive biomarkers, such as high CSF total tau, could aid the diagnostic process. However, discordant studies have led to controversies about the clinical value of some established surrogate biomarkers. Development and clinical application of disease-specific protein aggregation and amplification assays, such as real-time quaking induced conversion (RT-QuIC), have constituted major breakthroughs for the confident pre-mortem diagnosis of sporadic Creutzfeldt-Jakob disease. Updated criteria for the diagnosis of sporadic Creutzfeldt-Jakob disease, including application of RT-QuIC, should improve early clinical confirmation, surveillance, assessment of PrP Sc seeding activity in different tissues, and trial monitoring. Moreover, emerging blood-based, prognostic, and potentially pre-symptomatic biomarker candidates are under investigation.